Limb Length Discrepancy on an 11-Month-Old Boy with Osteoid Osteoma - Ana Cotta; Renato Cesar Rezende de Castro; Julia Filardi Paim; Leonardo Sardenberg Fiuza; Maria Henriqueta Freire Lyra (Revista Brasileira de Ortopedia)
Abstract Osteoid osteoma is a benign bone tumor that frequently occurs between the ages of 10 and 25 years old; in about 80% of the patients, it is associated with intense pain. The present article describes the case of an 11-month-old infant with claudication, right lower limb shortening, and painless right leg volume increase. Image studies demonstrated an osteolytic lesion with small ossifications within, involved by cortical thickening of the right tibial diaphysis. The diagnostic hypotheses were osteoid osteoma, chronic osteomyelitis (Brodie abscess), Ewing sarcoma, and Langerhans cell histiocytosis. Microorganismcultures were negative and the histopathological exam demonstrated osteoid osteoma. The present report expands the knowledge on osteoid osteoma as a cause of painless limping and lower limb shortening in infancy. The early differential diagnosis is important, as surgical excision is curative and prevents further complications.